Pengaruh Model Case Based Learning Berbantuan E-LKM Terhadap Keterampilan Berpikir Kritis dan Prestasi Belajar Matematika Murid SMA - Ni Ketut Sri Wedani; I Wayan Santyasa; I Komang Sudarma (Cetta: Jurnal Ilmu Pendidikan, 2026)
Low mathematics achievement among Indonesian students, evidenced by a PISA 2022 score of 354 points below the OECD average of 485, underscores the need for innovative pedagogy.The objective of this study was to examine the effect of a case-based learning (CBL) model integrated with Electronic Student Worksheets (E-LKM) on critical thinking skills and mathematics achievement, compared to CBL alone and Direct Instruction (DI). A quasi-experimental non-equivalent pretest-posttest control group design was employed at SMA Negeri 2 Amlapura, Bali, even semester 2025/2026. Three classes were selected through simple random sampling from 369 grade XI students: CBL+E-LKM (n = 35), CBL (n = 35), and DI (n = 34). Critical thinking skills were measured using essay-based tests and mathematics achievement using multiple-choice tests, analyzed with MANCOVA in IBM SPSS 26.0. Results revealed: (1) the three groups differed significantly in both variables simultaneously (Pillai's Trace F = 48.074; p < 0.001); (2) critical thinking skills differed significantly, with posttest means of CBL+E-LKM (M = 32.29; very high), CBL (M = 30.63; high), and DI (M = 24.32; high), F = 905.294, p < 0.001; and (3) mathematics achievement followed the same superiority order, CBL+E-LKM (M = 7.66), CBL (M = 7.26), and DI (M = 6.29), F = 139.284, p < 0.001. These findings confirm that integrating E-LKM into CBL simultaneously enhances critical thinking skills and mathematics achievement through authentic case contexts and adaptive digital scaffolding, making CBL+E-LKM a recommended model for higher-order thinking instruction in mathematics.